PELATIHAN DESAIN UNTUK PEMBUATAN MEDIA PEMBELAJARAN DAN PROMOSI DI VIHARA SUTRA MAITREYA - Andreas, Kevin; Bertnas Valentino, Calvin; Hartati, Ery; Fernando; Wijaya, Frisky (Politeknik Negeri Sriwijaya, 2024)
The rapid advancement of technology has created new demands for engaging and interactive learning media and promotional materials. In the educational context, attractive and interactive learning media can help increase learners' interest and understanding of the subject matter. However, many community organizations, such as the youth at Vihara Sutra Maitreya Palembang, lack the skills to leverage digital tools for creating visually appealing content. This community service project aimed to address this issue by providing training on using the Canva application to 14 youth members of Vihara Sutra Maitreya Palembang for designing learning media and promotional materials. The training was conducted in-person and adopted a persuasive approach, combining theoretical sessions on graphic design concepts, demonstrations of Canva's features, hands-on practice, and discussions. Based on the evaluation of the training using the Likert scale, participants gave a very good rating with an overall average score of 86.23%. Quantitative targets were achieved, with 92.85% demonstrating a good understanding of the material, all participants producing at least one usable design, and 100% active participation. This initiative successfully enhanced the vihara youth's ability to create attractive visual content for educational and promotional purposes within their community while leveraging technological advancements.